Psychological aspects of moral development of teenagers (on the example of studying Harper Lee’s novel “To Kill a Mockingbird”) (Actual Problems of Psychology in Educational Institutions, 2023)
The article is devoted to the problem of moral development ofmodern teenagers by means of school education. The essential dimensionsof the moral development of the individual are analyzed, the developmentof the moral consciousness of modern teenagers as an effect of thesocialization of the individual is outlined. The results of measuring the valueorientations of teenagers using the method of M. Rokych are presented.Special attention is paid to the development potential of foreign literature.The author examines in detail the educational and developmental resourceof Harper Lee’s novel “To Kill a Mockingbird” in the formation of themoral consciousness of the personality of older teenagers. The possibilitiesof this novel in the development of tolerance and sense of justice amongteenagers have been revealed.
Keywords: morality, moral development, tolerance, growing up, adolescence, psychological and pedagogical support